Impact of informal sector growth on water, sanitation and hygiene service provision: the case of Norton Town Council in Zimbabwe - Shekede, Sylivia (Midlands State University, 2017)
The informal sector has grown over years as people fail to get employment in the formal sector. In Zimbabwe, the sector is dominated by women and the majority of the people in the sector are aged 15 years to 30 years. Although the sector has made significant contributions to improving people`s livelihoods, the growth of the sector has impacted negatively on WASH service provision in urban areas as the existing WASH infrastructure was not designed to cater for these large numbers of people. More so, the WASH infrastructure is old, rusty and in most cases leaking resulting in poor service delivery across the majority of urban councils. The major challenges emanating from the growth of the informal sector in Norton, Zimbabwe include illegal dumping of solid waste, littering, blockage of water and sewer systems, pollution, vandalism of WASH infrastructure, non-payment of operating fees and poor hygiene practices. There is need for Norton Town Council to review existing by-laws to ensure guidelines for the regulation of the operations of informal sector are clearly defined. Furthermore, Norton Town Council should take into account the WASH needs of the informal sector in town planning for sustainable development.